The Use of English Camp to Improve English Speaking Skill - M. Era Azhari; Lalu Ferryawan Wahyu Mulia; Zainul Akbar; Rangkun Wari Gunawan; Selamet Riadi Jaelani (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This article focused on the effectiveness of English Camp for increasing English speaking skill. The aim of the study was to improve students’ speaking skill. This study was quantitative using experimental design, the population was 22 students but the sample was 11, Purposive sampling was taken from students who had the lowest pre-test scores, the speaking rubric score was used to assess students’ speaking abilities. The research instrument uses a list of questions about the material that has been taught during one week. The average score of pre-test was 5.81 and the average score of post-test was 10.09. English camp also allowed teachers to experiment various methods in every meeting.